ACNPD: The Database for Elucidating the Relationships Between Natural Products, Compounds, Molecular Mechanisms, and Cancer Types - Tan, Xiaojie; Fu, Jiahui; Yuan, Zhaoxin; Zhu, Lingjuan; Fu, Leilei (Frontiers in Pharmacology, 2021)
Objectives: Cancer refers to a collection of diseases of uncontrolled proliferation of cells caused by mutated genes which are generated by external or internal factors. As the mechanism of cancers has been constantly revealed, including cell cycle regulation, proliferation, apoptosis and so on, anti-cancer drugs acting on each stage have also been developed. It is worth noting that natural products are one of the important sources for the development of anti-cancer drugs. Nevertheless, to the best of our knowledge, there is not any database summarizing the relationships between natural products, compounds, molecular mechanisms, and cancer types. Materials and methods: Based on published literatures and other data sources, we have constructed an anti-cancer natural product database (ACNPD) (http://www.acnpd-fu.com/). At present, the database includes 521 compounds from herbs and 1,593 specific Pharmacological regulation mechanism covering 10 common cancer types such as breast, lung and cervical cancer. Results: Integrating existing data sources, we have obtained a large amount of information on natural anti-cancer products, including herbal sources, regulatory targets and pathways. ACNPD is a valuable online resource that illustrates the complex pharmacological relationship between natural products and tumors. Conclusions: ACNPD is crucial to better understanding the relationships between traditional Chinese medicine (TCM) and cancer, which is not only conducive to expand the influence of TCM, but help to find more new anti-cancer drugs in the future.